2023
DOI: 10.1002/ptr.8022
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the therapeutic promise of natural products in alleviating drug‐induced liver injury: Present advancements and future prospects

Deepti Singh,
Mohammad Afsar Khan,
Hifzur R. Siddique

Abstract: Drug‐induced liver injury (DILI) refers to adverse reactions to small chemical compounds, biological agents, and medical products. These reactions can manifest as acute or chronic damage to the liver. From 1997 to 2016, eight drugs, including troglitazone, nefazodone, and lumiracoxib, were removed from the market due to their liver‐damaging effects, which can cause diseases. We aimed to review the recent research on natural products and their bioactive components as hepatoprotective agents in mitigating DILI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 147 publications
0
5
0
Order By: Relevance
“…India, a country well-known for its biodiversity, is home to some 40,000 plant species, 15,000 of which are thought to offer therapeutic benefits. In India, communities use 7,000-7,500 plants to treat a range of illnesses Kotmire et al (2024), Ali & Datusalia (2024), Singh et al (2024). Numerous plant species are used in the many native medical systems, including Ayurveda, Siddha, and Unani, to cure various illnesses Sane (2002), Farnsworth et al (1985), Abraham & Paridhavi (2013), Kunwar et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…India, a country well-known for its biodiversity, is home to some 40,000 plant species, 15,000 of which are thought to offer therapeutic benefits. In India, communities use 7,000-7,500 plants to treat a range of illnesses Kotmire et al (2024), Ali & Datusalia (2024), Singh et al (2024). Numerous plant species are used in the many native medical systems, including Ayurveda, Siddha, and Unani, to cure various illnesses Sane (2002), Farnsworth et al (1985), Abraham & Paridhavi (2013), Kunwar et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor, We read with great interest a recent review by Singh et al (2023) in Phytotherapy Research summarizing a literature search on the use of natural products in drug-induced liver injury (DILI). As acetaminophen (APAP) overdose is the clinically most relevant drug hepatotoxicity and the mechanisms of cell death and organ injury are by far better understood than any other form of DILI (Jaeschke & Ramachandran, 2024;Ramachandran et al, 2018), the focus of the review was not unexpectedly mainly on APAP.…”
mentioning
confidence: 99%
“…As acetaminophen (APAP) overdose is the clinically most relevant drug hepatotoxicity and the mechanisms of cell death and organ injury are by far better understood than any other form of DILI (Jaeschke & Ramachandran, 2024;Ramachandran et al, 2018), the focus of the review was not unexpectedly mainly on APAP. The authors concluded based on the list of papers from their search that natural products "prevent mitochondrial dysfunction and inflammation, inhibiting oxidative/nitrative stress, and macromolecular damage," and so on and then suggest randomized clinical trials to test their clinical efficacy (Singh et al, 2023). However, the problem is that Singh et al (2023) took most of the mechanistic conclusions of these natural product papers at face value.…”
mentioning
confidence: 99%
See 2 more Smart Citations